Pulmonary toxicity and lung tumorigenic potential of surrogate metal oxides in gas metal arc welding–stainless steel fume: Iron as a primary mediator versus chromium and nickel - Falcone, Lauryn M.; Erdely, Aaron; Salmen, Rebecca; Keane, Michael; Battelli, Lori; Kodali, Vamsi; Bowers, Lauren; Stefaniak, Aleksandr B.; Kashon, Michael L.; Antonini, James M.; Zeidler-Erdely, Patti C. (PloS one, 2018)
In 2017, the International Agency for Research on Cancer classified welding fumes as "carcinogenic to humans" (Group 1). Both mild steel (MS) welding, where fumes lack carcinogenic chromium and nickel, and stainless steel (SS) increase lung cancer risk in welders; therefore, further research to better understand the toxicity of the individual metals is needed. The objectives were to (1) compare the pulmonary toxicity of chromium (as Cr(III) oxide [Cr2O3] and Cr (VI) calcium chromate [CaCrO4]), nickel [II] oxide (NiO), iron [III] oxide (Fe2O3), and gas metal arc welding-SS (GMAW-SS) fume; and (2) determine if these metal oxides can promote lung tumors. Lung tumor susceptible A/J mice (male, 4-5 weeks old) were exposed by oropharyngeal aspiration to vehicle, GMAW-SS fume (1.7 mg), or a low or high dose of surrogate metal oxides based on the respective weight percent of each metal in the fume: Cr2O3 + CaCrO4 (366 + 5 μg and 731 + 11 μg), NiO (141 and 281 μg), or Fe2O3 (1 and 2 mg). Bronchoalveolar lavage, histopathology, and lung/liver qPCR were done at 1, 7, 28, and 84 days post-aspiration. In a two-stage lung carcinogenesis model, mice were initiated with 3-methylcholanthrene (10 μg/g; intraperitoneal; 1x) or corn oil then exposed to metal oxides or vehicle (1 x/week for 5 weeks) by oropharyngeal aspiration. Lung tumors were counted at 30 weeks post-initiation. Results indicate the inflammatory potential of the metal oxides was Fe2O3 > Cr2O3 + CaCrO4 > NiO. Overall, the pneumotoxic effects were negligible for NiO, acute but not persistent for Cr2O3 + CaCrO4, and persistent for the Fe2O3 exposures. Fe2O3, but not Cr2O3 + CaCrO4 or NiO significantly promoted lung tumors. These results provide experimental evidence that Fe2O3 is an important mediator of welding fume toxicity and support epidemiological findings and the IARC classification.